Assuming the ecosexual position : the Earth as lover - Sprinkle, Annie, 1954-; Stephens, Beth; Klein, Jennie (Book collections on Project MUSE., 2021)
"The story of the artistic collaboration between the originators of the ecosex movement, their diverse communities, and the Earth"--